Pengaruh Jenis Kemasan Terhadap Umur Simpan Buah Nanas Madu (Ananas comosus (L.) Merr.) - Deglas, Welly; Hendrik, Hendrik (Jurnal Ilmu Pangan dan Hasil Pertanian, 2024)
The aim of this research was to investigate the impact of various types of plastic packaging on the physical characteristics, weight, sugar content, and shelf life of honey pineapple (Ananas Comosus (L.) Merr.). Additionally, this study aimed to evaluate the influence of Polypropylene (PP) and High Density Polyethylene (HDPE) plastic packaging on the sensory evaluation of honey pineapple fruit following storage. Employing a Completely Randomized Design (CRD) with three replications, treatments included no packaging, Polypropylene (PP) plastic packaging, and High Density Polyethylene (HDPE). Research parameters encompassed the physical and chemical properties of honey pineapple fruit, such as weight loss, color, aroma, texture, and sugar content.Findings revealed that honey pineapple subjected to treatment (P1) exhibited the lowest weight loss percentage (0.04%), contrasting with the highest weight loss observed in P0 (11.6%). ANOVA analysis of the scoring test indicated no significant differences in color, aroma, or texture. Honey pineapple fruit under treatment P2 demonstrated the lowest percentage of total sugar content compared to P0 and P1. Regarding physical appearance, honey pineapple fruit treated with P0 displayed the most pronounced change in aroma. According to the experimental assessment based on SNI 3166-2009, honey pineapple fruit without packaging failed to meet quality criteria, while those packaged in Polypropylene (PP) and High Density Polyethylene (HDPE) plastic met the quality standards for honey pineapple.